SELF-EFFICACY, EMOTION REGULATION, AND RESILIENCE OF FORMAL WORKING MOTHERS DURING THE COVID-19 PANDEMIC - Nadia Rahmania; Risda Rizkillah; Musthofa (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Resilience can give an individual the strength to face stressful situations and view life positively. The purpose of this study was to analyze the influence of self-efficacy and emotion regulation on the resilience of mothers who work in the formal sector during the Covid-19 pandemic. The research design used was cross-sectional, and the research location was determined using a purposive technique based on the high number of Covid-19 cases at the time of the study, so DKI Jakarta and West Java were chosen. Primary data was collected through questionnaires distributed online via a google form. The sampling technique used voluntary sampling with the respondent's criteria: formal working mothers with school-age children and intact families in DKI Jakarta and West Java Provinces. The number of respondents in this study was 101 people. Data were analyzed using correlation and regression tests. Results showed that self-efficacy, emotion regulation, and resilience were positively related and more than half of mothers had moderate self-efficacy, emotion regulation, and resilience. The regression test results stated that self-efficacy, emotion regulation, and daughters positively affected the mother's resilience. Meanwhile, the father's age had a negative effect on the mother’s resilience.